A Comparative Study on Shear Wall Concept in Accordance to its Seismic Behavior - U, Deepna; S Menon, Arjun; Balamurugan, S (International Journal of Engineering and Technology, 2018)
The consequences of lateral loads like earthquake loads, wind loads and blast forces are achieving utmost concern nowadays. Imparting sufficient strength and stability in counter to the lateral loads is one of the major challenges faced by every designer. Therefore Proper understanding of the Seismic performance of different types of shear walls is necessary for structural engineers so as to safeguard the structure against lateral loads. The present paper describes the comparison of the seismic performance of high rise buildings and optimizing the thickness of RCC shear wall, Steel Plate Shear Wall (SPSW) and composite shear wall for (G+20) stories. The design and analysis of theÂ building with RCC shear wall, steel plate shear wall and composite shear wall is carried out using software ETABS. Effect of varying thickness of shear panels and comparison of the results of story drift and story shear is presented.Â Â